1982
DOI: 10.1177/002246698201600407
|View full text |Cite
|
Sign up to set email alerts
|

Designing Spelling Instruction for Learning-Disabled Children: An Emphasis on Unit Size, Distributed Practice, and Training for Transfer

Abstract: This paper describes an intervention designed to enhance spelling achievement for learning-disabled (LD) elementary school children. A total of 39 LD children were instructed for 8 sessions over a period of 3 weeks. An experimental group ( n = 24) was taught with lessons that incorporated reduced unit size, distributed practice and review, and training for transfer, and a comparison group ( n = 15) with methods that are typically used in the teaching of spelling. While all children could spell less than 10% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
23
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 5 publications
2
23
0
Order By: Relevance
“…In the past decades, research has revealed that adequate spelling performance requires formal spelling instruction (e.g., Bosman, 2004;Butyniec-Thomas & Woloshyn, 1997;Devonshire & Fluck, 2010;Faber, 2006;Gettinger, Bryant, & Fayne, 1982;Graham, 1999Graham, , 2000. Numerous studies focused on the best ways to memorize a word's spelling (e.g., Bosman, van Hell, & Verhoeven, 2006;Hilte & Reitsma, 2006;Hubbert, Weber, & McLaughlin, 2000); ways to learn a spelling rule (e.g., Darch, Eaves, Crowe, Simmons, & Conniff, 2006;Hilte & Reitsma, 2011;Kemper, Verhoeven, & Bosman, 2012); and how to encourage students to apply spelling rules in a structured way (e.g., Butyniec-Thomas & Woloshyn, 1997;Paffen & Bosman, 2005).…”
Section: Intervention Typementioning
confidence: 99%
“…In the past decades, research has revealed that adequate spelling performance requires formal spelling instruction (e.g., Bosman, 2004;Butyniec-Thomas & Woloshyn, 1997;Devonshire & Fluck, 2010;Faber, 2006;Gettinger, Bryant, & Fayne, 1982;Graham, 1999Graham, , 2000. Numerous studies focused on the best ways to memorize a word's spelling (e.g., Bosman, van Hell, & Verhoeven, 2006;Hilte & Reitsma, 2006;Hubbert, Weber, & McLaughlin, 2000); ways to learn a spelling rule (e.g., Darch, Eaves, Crowe, Simmons, & Conniff, 2006;Hilte & Reitsma, 2011;Kemper, Verhoeven, & Bosman, 2012); and how to encourage students to apply spelling rules in a structured way (e.g., Butyniec-Thomas & Woloshyn, 1997;Paffen & Bosman, 2005).…”
Section: Intervention Typementioning
confidence: 99%
“…The instructional procedures for this study include error analysis, modeling, and mastery for all three motor conditions. Unit size is another area of investigation related to the spelling performance of students with LD (Bryant, Drabin, & Gettinger, 1981;Gettinger, Bryant, & Fayne, 1982). Bryant et al defined unit size as the number of words taught within a single instructional period.…”
mentioning
confidence: 99%
“…This is in contrast to professionals who view a learning disability as specific in nature and circumscribed in severity (Johnson & Myklebust, 1967;Millon, 1969;Siegel, 1974). Clinicians working with students who have a learning disability emphasize the efficacy of compensatory strategies and/or corrective work through remediation (Geschwind, 1982;Gettinger, Bryant, & Fayne, 1982;Licht, 1983;Reynolds & Birch, 1977;Spano, 1981;Torgesen & Licht, 1983). If youngsters were to accept the practitioner's view of the specific, circumscribed nature of their disability, they might be less likely to form negative self-evaluations.…”
mentioning
confidence: 99%